Moving from the Known to the Unknown in Academic Writing. - Pfeiffer, Verbra Frances (Cambridge Scholars Publishing, 2022)
Expressive writing is mainly used on psychological patients to assist them in dealing with their trauma. This book is the first to use expressive writing in assisting L2 students in their academic writing. As may be shown in this book that using expressive writing techniques are particularly helpful for L2 students who have difficulty expressing themselves when writing in English. The book will appeal to lecturers in language centres, linguists, psychologists, and teachers.